Indium-mediated reductive dehalogenation of alpha-halocarbonyl compounds in water - PARK, LEEYOUNG; KEUM, GYO CHANG; Kang, Soon Bang; Kim, KS; Kim, You Seung (ROYAL SOC CHEMISTRY, 2000)
Reactions of various alpha -halocarbonyl compounds 1 with indium in the presence of a catalytic amount of sodium dodecyl sulfate in water were performed to afford the corresponding parent carbonyl compounds 2 in excellent yields.